Implementation of Reuse and Recycle Models as an Effort to Fulfill Fish Feed for Fisherman’s Cage in Kedung Ombo - Dewi Ismoyowati; Izza Mafruhah; Nurul Istiqomah; Nunung Sri Mulyani (Journal of Innovation and Community Engagement, 2023)
The purpose of this service is the development of the fishery sector by utilizing the remaining production (reuse and recycle) as an effort to preserve the environment and increase the circular economy. These objectives are derived in specific objectives: 1) Development of processed fish food to fulfill the needs of independent fish feed; and 2) Making fish feed based on local potential and recycling fish processing residue. The service uses training and mentoring methods. The training is expected to provide skills to the community, especially in the manufacture of fish feed made from leftovers. The training was continued with mentoring by involving elements of students on an ongoing basis. Another method used is Focus Group Discussion (FGD). The result of this service is the growing independence of aquaculture fishermen and empowerment in improving their welfare.